Sport and exercise during viral acute respiratory illness - Time to revisit - Ruuskanen, O.; Valtonen, M.; Waris, M.; Luoto, R.; Heinonen, O.J. (Journal of Sport and Health Science, 2024)
Athletes are commonly advised not to compete or train during major symptoms of a viral acute respiratory illness (ARI), which most commonly is a common cold. It has been traditionally thought that heavy physical stress could induce the worsening of symptoms of ARI and possibly cause potentially severe complications like myocarditis or sudden cardiac death (SCD). In addition, viral ARI may decrease athlete's performance.1 These concerns have been recently stressed during the coronavirus disease 2019 (COVID-19) pandemic.2 However, it is anecdotally well-known that athletes commonly compete while experiencing common colds, most commonly due to picornaviral ARIs. In this perspective, we discuss what is known or not known regarding the risks of exercising during the viral ARI.